Genomic DNA methylation distinguishes subtypes of human focal cortical dysplasia. (10th May 2019) - Kobow, Katja; Ziemann, Mark; Kaipananickal, Harikrishnan; Khurana, Ishant; Mühlebner, Angelika; Feucht, Martha; Hainfellner, Johannes A.; Czech, Thomas; Aronica, Eleonora; Pieper, Tom; Holthausen, Hans; Kudernatsch, Manfred; et al.
Abstract: Objectives: Focal cortical dysplasia (FCD) is a major cause of drug‐resistant focal epilepsy in children, and the clinicopathological classification remains a challenging issue in daily practice. With the recent progress in DNA methylation–based classification of human brain tumors we examined whether genomic DNA methylation and gene expression analysis can be used to also distinguish human FCD subtypes. Methods: DNA methylomes and transcriptomes were generated from massive parallel sequencing in 15 surgical FCD specimens, matched with 5 epilepsy and 6 nonepilepsy controls. Results: Differential hierarchical cluster analysis of DNA methylation distinguished major FCD subtypes (ie, Ia, IIa, and IIb) from patients with temporal lobe epilepsy patients and nonepileptic controls. Targeted panel sequencing identified a novel likely pathogenic variant in DEPDC5 in a patient with FCD type IIa. However, no enrichment of differential DNA methylation or gene expression was observed in mechanistic target of rapamycin (mTOR) pathway–related genes. Significance: Our studies extend the evidence for disease‐specific methylation signatures toward focal epilepsies in favor of an integrated clinicopathologic and molecular classification system of FCD subtypes incorporating genomic methylation.